Targeted immobilisation of lysozyme in the enamel pellicle from different solutions - Hannig, Christian; Spitzmüller, Bettina; Hoth-Hannig, Wiebke; Hannig, Matthias (Clinical oral investigations, 2011)
Mouthwashes containing protective enzymes are required especially for patients suffering from xerostomia. The present study aimed to investigate the possibilities of modulating the immobilisation of lysozyme in the in situ pellicle layer. In situ formed pellicles were incubated in vitro for 10 min with various enzymatic buffer solutions containing lysozyme and additive enzymes such as transglutaminase or trypsin as well as polyphenolic compounds (cistus tea). After the rinses, the pellicle samples were incubated in collected whole saliva or in desorption solutions for 0, 20 and 40 min and the enzyme activities were measured. Furthermore, accumulation of lysozyme in the pellicle was visualised in ultrathin sections of the pellicle using the gold immunolabelling technique and transmission electron microscopy. Hen egg white lysozyme was accumulated in the in situ pellicle tenaciously. Up to 2.8-fold higher activities than in controls were observed. The addition of transglutaminase did not enhance the immobilisation of lysozyme activity, whereas the polyphenolic compound had no adverse effect. Accumulation of lysozyme in the acquired pellicle was confirmed by gold immunolabelling. Targeted and tenacious immobilisation of lysozyme in the acquired pellicle is possible. Poylphenolic compounds might be a relevant additive for mouthwashes containing lysozyme.